La pluralité du moi dans quelques textes médiévaux - Helder Godinho (Carnets)
The texts and the characters hear referred to, show us characters who have a double identity when it comes to persons with an important role in history: empire makers, heroes, saints, for example. They have a double nature, human and divine, as Aeneas or Heracles, or even the saints created by a direct intervention of God. Others have a nature only human but which is formed by several actors, as Utherpendragon, King Arthur’s father. These facts are interpreted as being a way of referring to the complexity of the ego with the conceptual utensils of the epoch.